DIAGNOSTIC ACCURACY OF MAGNETIC RESONANCE IMAGING FOR DIAGNOSIS OF ACUTE INVASIVE FUNGAL SINUSITIS TAKING HISTOPATHOLOGY AS A GOLD STANDARD - Waqar, Sehrish; Ameer, Saima; Naeem, Muhammad; Bajwa, Mubashar Ahmed; Bajwa, Saman Mubashar; Bajwa, G. R (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find the diagnostic accuracy of magnetic resonance imaging in diagnosing the Acute Invasive Fungal Sinusitis taking histopathology as a gold standard. Study Design: Retrospective study. Place and Duration of Study: Radiology Department of Doctor’s Trust Teaching Hospital, Sargodha, from Mar 2019 to Aug 2019. Methodology: The study was conducted in the Radiology Department of Doctor’s Trust Teaching Hospital affiliated with Rai Medical College, Sargodha from the period of March 2019 to August 2019. The size of the sample was 17 patients who were immune compromised and was diagnosed for acute fungal sinusitis. The magnetic resonance imaging scans were reviewed by the senior radiologist and histopathology reports and survival data was also recorded for the patients. Results: The diagnostic results of magnetic resonance imaging were sensitive and accurate in predicting the acute invasive fungal sinusitis in patients. The sensitivity of the results was 85% and the specificity of the results was 96%. The positive predictive value for magnetic resonance imaging was 94% and the negative predictive value for magnetic resonance imaging was also 96%. Conclusion: It was concluded from the study that magnetic resonance imaging is a sensitive diagnostic tool for predicting the acute invasive fungal sinusitis.